Chemical Analysis of Wheat Straw and Digested Slurry for Pulp & Paper Production - Kaur, Navjot (My University, 2017)
The wheat straw is seeing as alternate raw material for the production of pulp and paper due to less availability of woody raw material and environmental concerns. The chemical analysis of wheat straw and digested pulp were studied in the present work. The soda pulping method was adopted for the pulping of wheat straw. The soda pulping was done in lab scale pulp digester at various temperature and pressure. The temperature and pressure of the digester were maintained as 108-159 0C and 0.5-5.8 kgf/cm2. The feed rate of wheat straw and white liquor were varied as 70-87 g/l and 1-1.71 l/min, respectively. The composition of wheat straw was found as ash content 8.85%, cellulose content 40%, lignin content (acid-soluble + acid- insoluble) 18.3%, holocellulose content 68.1%, respectively. The digested slurry was also analysed in each case in terms of kappa number, klason lignin, total solids, residual alkali and viscosity of black liquor. The feed screw RPM 24 and white liquor flow rate 1.334 l/min., 13% NaOH concentration were found optimum values at 5.80 Kgf/cm2 pressure and 154 0C (tube 1) , 159 0C (tube 2) temperature. For this optimum case, the kappa number is 19.58 and total solids 5.4 g/l were obtained.
Keywords: Soda pulping; wheat straw; lignin; Kappa number; pulp; digester